Adsorption of As(III) Ions onto Iron-Containing Waste Sludge - Adina Negrea; Lavinia Lupa; Mihaela Ciopec; Radu Lazau; Cornelia Muntean; Petru Negrea (Adsorption Science & Technology)
The adsorption performance of a low-cost adsorbent (IS), viz. an iron-containing waste sludge arising during a hot-dip galvanizing process, towards the removal of As(III) ions from synthetic aqueous solutions and natural underground water was examined. The adsorption process was best described by the pseudo-second-order kinetic equation. The equilibrium adsorption data were well described by the Langmuir model. The value of the dimensional separation factor, R L , indicated favourable adsorption. The maximum adsorption capacity of IS was 625 μg As(III)/g. The variation in the extent of adsorption with temperature was used to evaluate the thermodynamic parameters for the adsorption process. The values of ΔH 0 and ΔG 0 obtained demonstrated that the adsorption process was exothermic and spontaneous. The studied material exhibited an excellent As(III) ion adsorption performance from both synthetic solutions and a natural water sample. Moreover, no secondary contaminated substances arise if the exhausted adsorbent is recycled (e.g. in glass applications).